INTEGRASI ILMU DAN ISLAM MENURUT M. AMIN ABDULLAH - Ardian Ardian (PT. Hasba Edukasi Mandiri, 2025)
The issue of the scientific dichotomy between Islamic sciences and general sciences, particularly within the Islamic Higher Education Institutions, has long been a serious topic of discussion, demanding fundamental epistemological reform. The main criticism highlights that the current pattern of development of Islamic sciences tends to be fragmentary and has not been able to establish a close connection with the dynamics and contemporary global issues. Amid this crisis, M. Amin Abdullah emerged as a thinker who offered a scientific reconstruction project through an integrative-interconnective paradigm. This idea aims to reconcile, connect, and unite religious reasoning with modern scientific and philosophical approaches, thus producing a holistic understanding of reality. This paper aims to present a descriptive-analytical analysis of the overall thinking of M. Amin Abdullah's Integration of Science and Islam. The discussion will focus on three main aspects: (1) his critique of scientific fragmentation, (2) the core concept of integration-interconnection, and (3) its philosophical foundation, namely theo-anthropocentric-integralistic epistemology visualized through a four-layer spider web concept map. Thus, this research contributes to strengthening understanding of the need for multidisciplinary, interdisciplinary, and transdisciplinary approaches in Islamic studies.